La maritimité sous les Tropiques : les contributions d’une étude réalisée à Fortaleza (Ceará) - Eustogio Wanderley Correia Dantas (Confins)
The maritime dimension in the tropics: contributions from a study in Fortaleza (Ceará) - At the end of the twentieth century everything related to the sea has become a social phenomenon. The images of the sea and of all things maritime, conveyed in developed countries, combined with socio -economic and technological changes, generated a stream highligting the coastal areas of developing countries. This kind of recovery, often traduced by the concept of tropism, appears in a strong bibliography marked by a dichotomous maritimity. On the one hand, external or modern maritime dimension, on the Western world. On the other hand, an internal or traditional maritime dimension, for tropical populations. Taking into account the valuation of coastal areas in Fortaleza (Ceará) allows to put into perspective this approach. In this coastal city, a local elite fascinated by the new maritime practices produces the same territories and maintains the same desires as in the West. Mainly in countries untouched by international tourism flows, this social phenomenon raises a cultural movement influenced by Western ways, and on sees a change in mentality of local groups towards the sea.